2015
DOI: 10.1097/mib.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Infliximab Are Associated with Lower Infliximab Levels and Increased Likelihood of Surgery in Pediatric IBD

Abstract: Background Adult studies suggest antibodies to infliximab (ATI) correlate with loss of response in inflammatory bowel disease but pediatric data are limited. Methods We conducted a cross-sectional study of trough infliximab levels and ATI in 134 pediatric and young adult patients receiving infliximab. At the time serum was obtained demographics, disease phenotype, duration of infliximab therapy, use of combination therapy (methotrexate or 6-mercaptopurine with infliximab), and surgery were recorded. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 32 publications
4
35
1
1
Order By: Relevance
“…Formation of antidrug antibodies has been linked to decreased serum drug concentrations and higher rates of loss of response 38 , 39 and surgery. 40 In our study, the prevalence of detectable antidrug antibodies was low. This could be expected because the study population consisted of long-term treatment responders, possibly leading to a selection of patients not developing antidrug antibodies.…”
Section: Discussioncontrasting
confidence: 51%
“…Formation of antidrug antibodies has been linked to decreased serum drug concentrations and higher rates of loss of response 38 , 39 and surgery. 40 In our study, the prevalence of detectable antidrug antibodies was low. This could be expected because the study population consisted of long-term treatment responders, possibly leading to a selection of patients not developing antidrug antibodies.…”
Section: Discussioncontrasting
confidence: 51%
“…Differences in serum biologic concentrations between ADAb-positive and -negative patients were found to be statistically significant in studies of ADA [4244, 4750, 5355, 57, 58, 61] and INF [54, 57, 58, 61, 8791, 97, 98, 105, 107, 111, 113, 114] across chronic inflammatory diseases. In the Biologics in Rheumatoid Arthritis Genetics and Genomics Study Syndicate, a 12-month observational prospective cohort study, ADAbs against ADA were detected in 31 of 160 (19%) ADA-treated patients and were significantly associated with lower ADA concentrations ( r s  = −0.51; p  < 0.0001) [44].…”
Section: Resultsmentioning
confidence: 99%
“…For studies included in this review in which serum levels of biologics were reported – ADM, CZP and IFX – ADAbs-positive patients had lower serum levels of the biologic than ADAbs-negative patients ( Table 2 ). 27 48 …”
Section: Resultsmentioning
confidence: 99%